Treatment Outcomes for Extensively Drug-Resistant Tuberculosis and HIV Co-infection - O’Donnell, Max R.; Padayatchi, Nesri; Kvasnovsky, Charlotte; Werner, Lise; Master, Iqbal; Horsburgh, C. Robert (Emerging infectious diseases, 2013)
High mortality rates have been reported for patients co-infected with extensively drug-resistant tuberculosis (XDR-TB) and HIV, but treatment outcomes have not been reported. We report treatment outcomes for adult XDR TB patients in KwaZulu-Natal Province, South Africa. Initial data were obtained retrospectively, and outcomes were obtained prospectively during 24 months of treatment. A total of 114 XDR TB patients were treated (median 6 drugs, range 3-9 drugs); 82 (73%) were HIV positive and 50 (61%) were receiving antiretroviral therapy. After receiving treatment for 24 months, 48 (42%) of 114 patients died, 25 (22%) were cured or successfully completed treatment, 19 (17%) withdrew from the study, and 22 (19%) showed treatment failure. A higher number of deaths occurred among HIV-positive patients not receiving antiretroviral therapy and among patients who did not show sputum culture conversion. Culture conversion was a major predictor of survival but was poorly predictive (51%) of successful treatment outcome.